Mechanisms involved in IL-15 superagonist enhancement of anti-PD-L1 therapy - Karin M. Knudson; Kristin C. Hicks; Sarah Alter; Jeffrey Schlom; Sofia R. Gameiro (Journal for ImmunoTherapy of Cancer, 2019)
Abstract Background Immunotherapy targeting PD-1/PD-L1 fails to induce clinical responses in most patients with solid cancers. N-803, formerly ALT-803, is an IL-15 superagonist mutant and dimeric IL-15RαSushi-Fc fusion protein complex that enhances CD8+ T and NK cell expansion and function and exhibits anti-tumor efficacy in preclinical models. Previous in vitro studies have shown that IL-15 increases PD-L1 expression, a negative regulator of CD8+ T and NK cell function. Most reported preclinical studies administered N-803 intraperitoneally not subcutaneously, the current clinical route of administration. N-803 is now being evaluated clinically in combination with PD-1/PD-L1 inhibitors. However, the mechanism of action has not been fully elucidated. Here, we examined the antitumor efficacy and immunomodulatory effects of combining N-803 with an anti-PD-L1 antibody in preclinical models of solid carcinomas refractory to anti-PD-L1 or N-803. Methods Subcutaneous N-803 and an anti-PD-L1 monoclonal antibody were administered as monotherapy or in combination to 4T1 triple negative breast and MC38-CEA colon tumor-bearing mice. Anti-tumor efficacy was evaluated, and a comprehensive analysis of the immune-mediated effects of each therapy was performed on the primary tumor, lung as a site of metastasis, and spleen. Results We demonstrate that N-803 treatment increased PD-L1 expression on immune cells in vivo, supporting the combination of N-803 and anti-PD-L1. N-803 plus anti-PD-L1 was well-tolerated, reduced 4T1 lung metastasis and MC38-CEA tumor burden, and increased survival as compared to N-803 and anti-PD-L1 monotherapies. Efficacy of the combination therapy was dependent on both CD8+ T and NK cells and was associated with increased numbers of these activated immune cells in the lung and spleen. Most alterations to NK and CD8+ T cell phenotype and number were driven by N-803. However, the addition of anti-PD-L1 to N-803 significantly enhanced CD8+ T cell effector function versus N-803 and anti-PD-L1 monotherapies, as indicated by increased Granzyme B and IFNγ production, at the site of metastasis and in the periphery. Increased CD8+ T cell effector function correlated with higher serum IFNγ levels, without related toxicities, and enhanced anti-tumor efficacy of the N-803 plus anti-PD-L1 combination versus either monotherapy. Conclusions We provide novel insight into the mechanism of action of N-803 plus anti-PD-L1 combination and offer preclinical proof of concept supporting clinical use of N-803 in combination with checkpoint inhibitors, including for patients non- and/or minimally responsive to either monotherapy.